Accelerated gap collapse in a Slater antiferromagnet - Picano, Antonio; Eckstein, Martin (Physical Review B, 2021)
We study the melting of long-range antiferromagnetic order in the Hubbard model after an interaction quench, using nonequilibrium dynamical mean-field theory. From previous studies, the system is known to quickly relax into a prethermal symmetry-broken state. Using a convergent truncation of the memory integrals in the Kadanoff Baym equations, we unravel the subsequent relaxation dynamics of this state over several orders of magnitude in time. At long times, the prethermal state can be characterized by a single slow variable, which is related to the conduction band population. The dynamics of this variable is highly nonlinear, with a pronounced speedup once the gap falls below a certain value. This behavior indicates that nonthermal order can be self-sustained on some timescale because of a thermalization bottleneck is provided by the gap opened by the long-range order itself. These results cannot be reproduced using simple Fermi's golden rule estimate for the evolution of the conduction band population, and are distinct from the conventional scenario for the relaxation of prethermal states, in which a slow thermalization follows a rapid prethermalization.
CRIS-Team Scopus Importer:2021-04-30